Stability of Graphene on the Si (111) Surface: Insights from Reactive Molecular Dynamics Simulations - Didik Riyanto; Edy Kurniawan; Husein Muhammad Fras1; Hanifha Nur Azizah; Rizal Arifin (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2023)
The remarkable characteristics of graphene render it well-suited for a diverse range of applications, particularly in the realm of electronic devices. After the synthesis process, the two-dimensional material known as graphene is then transferred onto a substrate. Silicon (Si) is considered a suitable choice for this purpose. Therefore, it has become essential to investigate the stability of graphene on silicon surfaces. This study utilized reactive molecular dynamics simulations to investigate the thermal stability of graphene on a Si (111) substrate across a temperature range of 300 to 1500 K. The results demonstrate the exceptional stability of graphene on this particular surface. This phenomenon can be explained by the restricted intermolecular interactions between the carbon atoms in graphene and the silicon atoms on the substrate surface. The study findings indicate that graphene exhibits a dome-shaped configuration on the Si (111) surface. In this configuration, only the carbon atoms located at the periphery of the graphene structure interact with the silicon atoms present on the underlying substrate.